PADDY CROP COVERAGE IDENTIFICATION USING COMBINATION OF GREENNESS AND WETNESS FOR AGRICULTURAL CROPPING PATTERN CHANGE DETECTION - Shofyati, Rizatus; G.P, Dwi Kuncoro (GEOMATIKA, 2010)
Rice, as a staple food for Indonesian, should be continuously available and at the purchasable level of price. It is of great significance to obtain the paddy crop condition information at early stages in the paddy growing season. Along with the development of remote sensing applications, satellite data have become the uppermost data source to monitor large-scale crop condition. In the last twenty years, more than a dozen of methods based on remote sensing data were developed to monitor crop condition. Time series of NDVI and Wetness of Tasseled Cap Transformation derived from Landsat TM during the crop season (June to October 2004) have been used for analyzing the cropping pattern. The logical inference analysis based on knowledge of paddy growing stage can produce the crop calendar matrix. This study is attempted to describe alternative methods of remote sensing techniques to monitor agricultural condition. Further analysis on such data and information would be useful for considering a reasonable planning of agricultural management.Keywords: agricultural copping pattern, wetness, greenness, logical inference analysis.ABSTRAKBeras, sebagai makanan pokok untuk bangsa Indonesia, harus terus menerus tersedia dan dapat dibeli dengan harga terjangkau. Sehingga sangatlah penting untuk mendapatkan informasi kondisi tanaman padi pada tahap awal musim tanam padi. Seiring dengan perkembangan aplikasi penginderaan jauh, data satelit telah menjadi sumber data penting untuk memantau kondisi tanaman pada skala besar. Dalam dua puluh tahun terakhir, telah banyak metode menggunakan data penginderaan jauh yang dikembangkan untuk memantau kondisi tanaman. NDVI dan kelembaban berdasarkan analisis Tasseled Cap Transformation dari Landsat TM selama musim tanam (Juni sampai dengan Oktober 2004) telah digunakan untuk menganalisis pola tanam. Analisis logical inference berdasarkan pengetahuan dan pengalaman dari tahap pertumbuhan padi dapat menghasilkan matriks kalender tanam. Studi ini dilakukan untuk menjelaskan alternatif metode atau teknik penginderaan jauh untuk memantau kondisi pertanian. Analisis lebih lanjut pada data dan informasi akan berguna untuk mempertimbangkan perencanaan pengelolaan pertanian yang lebih proporsional. Kata Kunci: pola tanam pertanian, kelembaban, kehijauan, analisis logical inference.